Innovation Process In An Organization About Thematic Learning In Primary Schools; An Innovation Diffusion Research - Latip, Asep Ediana; Suparman, Atwi; Nadiroh, (International Journal of Psychosocial Rehabilitation, 2020)
Thematic learning as an innovative learning is determined as learning that must be implemented in primary schools. The purpose of this study aims to describe innovation process in an organizations about thematic learning in Primary Schools. This study uses a diffusion research procedure developed by Rogers. The research question is whether Primary schools have an initiation of thematic learning innovation? has the Primary School implemented thematic learning innovations? Does the Primary School redefine or restructure the implementation of thematic learning innovations? Does the Primary School make a process of clarification of thematic learning innovation? Has the Primary School been continuously implementing thematic learning?. The technique of collecting data uses a questionnaire with a Likkert scale. Sources of research data were obtained from members of the organization namely Principals and Teachers primary school. The sampling technique used is purposive sampling. Analysis of the data used is descriptive analysis. The results showed that thematic learning innovations have been diffused in pimary school which states that schools have an initiation of thematic learning innovations by setting agendas and matching with the needs of schools as an organization. In addition, members of the organization both principals and teachers stated that thematic learning implementation has been implemented by restructuring the organization, and has become part of the activities of organizational members and has become a regular schedule of learning activities in Primary schools.